(untitled) (Bangladesh Journal of Botany, 2022)
Consumption of diversified pigmented whole grain maize is encouraged to combat hidden hunger. The present research was conducted to evaluate physico-functional and nutritional properties of pigmented and non-pigmented maize in Bangladesh. Results revealed that white maize had the highest brightness value while purple, and deep red maize showed the lowest brightness value. The lowest bulk density (0.565 ± 0.005 g/ml) and percentage change (15.05 ± 0.31%) in sedimentation was in purple maize flour. White maize flour showed the highest change (35.43 ± 0.59%) in sedimentation value. Red and purple maize contained the highest amount of ash (2.27 ± 0.059 and 2.27 ± 0.05%, respectively) and mixed maize contained the highest crude fibre (4.17 ± 0.049%). Purple, deep red, and mixed colored maize had the highest (72 to 73%) carbohydrate whereas indigenous deep red and mixed colored maize had the lowest (6%) protein content. All most all samples had similar Mg and S content. Purple, deep red and mixed maize were found to be promising for Ca. White maize had the highest amount (19.79 ± 0.1 mg/100 g) of Zn. Yellow maize showed to contain the highest amount (4.99 ± 0.37 mg/100 g) of Fe. Overall, whole grain pigmented and nonpigmented hybrid and indigenous maize were comparable for physico-functional and nutritional properties. Bangladesh J. Bot. 51(3): 589-596, 2022 (September)